Analysis of the Visual to Verbal Mathematical Representation Process for Junior High School Students in Solving HOTS Questions in terms of Adversity Quotient - Muchammad Islam Fudin; Hendarto Cahyono; Octavina Rizky Utami Putri (Mathematics Education Journal, 2022)
Representation is a tool to solve a problem in the form of interpretation of what students think of a problem in the form of visual, verbal, and algebraic or symbolic representations. Solving non-routine problems in mathematics learning requires high order thinking skills (HOTS). Solving student problems, both routine and non-routine problems can be influenced by the ability of students to process existing problems into a challenge that must be passed, which is called Adversity Quotient. The purpose of this study was to describe the process of visual to verbal mathematical representation of junior high school students in solving HOTS questions in terms of the adversity quotient. The research uses a qualitative approach, the type of research used in this research is descriptive qualitative research. The data obtained in the form of written test results data, questionnaire results data and interview data will be submitted in written or oral form in narrative form. The instruments used are in the form of tests and questionnaires. The result show that the subject representation process with the adversity quotient level for the climber category has met the representation process indicators well in the three HOTS questions that were worked on. Subjects with the adversity quotient level in the camper category have not been able to meet the indicators of the representation process in the HOTS problem of creating.